PENERAPAN METODE BERMAIN DALAM MENGEMBANGKAN KECERDASAN LOGIKA MATEMATIKA ANAK USIA 5-6 TAHUN DI TKIT BAITUSSALAM TAHUN AJARAN 2018/2019 - Mawaddah Pasaribu; Mesiono Mesiono; Fauziah Nasution (Universitas Islam Negeri Sumatera Utara, 2019)
This study aims to determine the method of play in developing mathematical logic intelligence of children aged 5-6 years at TKIT Baitus with regards to various problems and how to solve them. This research is qualitative research. Data in this study used observation, interviews and documentation. Analysis of the data used is data reduction, data presentation and drawing conclusions. This research was carried out in the Baitussalam group B TKIT with a total of 20 children. The results of this study revealed four findings, namely: 1) The method of playing children aged 5-6 years at TKIT Baitus has been going well. 2) The development of mathematical logic intelligence of children aged 5-6 years has gone well. (3) The method of playing in developing mathematical logic intelligence of children aged 5-6 years has gone well according to the planning and assessment that has been made. (4) Supporting factors and obstacles to the implementation of playing methods in developing mathematical logic intelligence of children aged 5-6 years are already going well.